The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10773-012-1160-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Entropy of a Four-Level Atom with Arbitrary Nonlinearities

Abstract: General formalisms of a four-level atom in different configurations interacting with a single mode quantized electromagnetic field under multi-photon process with additional forms of nonlinearities of both the field and the intensity-dependent atom-field coupling are investigated. Analytical expressions for the time unitary evolution operator and density operator are obtained. The atom is prepared in its upper most and the field is prepared in a binomial state. The effects of the mean photon number, photon mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…We end this subsection with an overview on the mean photon number distribution in an explicit manner [33,61]. By using the first relation in Eq.…”
Section: Quantum Statistics: Mandel Parameter and Mean Photon Number ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We end this subsection with an overview on the mean photon number distribution in an explicit manner [33,61]. By using the first relation in Eq.…”
Section: Quantum Statistics: Mandel Parameter and Mean Photon Number ...mentioning
confidence: 99%
“…Once an atom and a radiation field are entangled with each other, the atom can be fully controlled by photons of the field. Many authors have found the degree of entanglement (DEM) in engineered interactions between two-, three-and four-level atoms with cavity field while different conditions have been taken into account [31][32][33]. Even though a lot of attention has been paid to two two-level atoms interacting with different field modes [34] (including additional interacting terms [35]), as well as one three-level atom interacting with various types of fields [21,22], to the best of our knowledge, the interaction between two three-level atoms with even a single-mode field, its exact and entire wavevector solution and the consequent physical properties have still not appeared in literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the left plots (f (n) = 1) of figures 4 and 5, Mandel parameter varies between positive and negative values, which means that the photons display super-or sub-Poissonian statistics for different intervals of times, alternatively. We end this subsection with an overview on the mean photon number distribution in an explicit manner [41,65]. By using Eq.…”
Section: Quantum Statisticsmentioning
confidence: 99%
“…We end this subsection with an overview on the mean photon number distribution in an explicit manner. [41,65] By using Eq. ( 25), in Figs.…”
Section: Quantum Statisticsmentioning
confidence: 99%
See 1 more Smart Citation